Meta-Analysis Enables Prediction of the Maximum Permissible Arsenic Concentration in Asian Paddy Soil - Mandal, Jajati; Sengupta, Sudip; Sarkar, Soumyajit; Mukherjee, Abhijit; Wood, Michael D.; Hutchinson, Simon M.; Mondal, Debapriya (Frontiers in Environmental Science, 2021)
It is now well-established that not just drinking water, but irrigation water contaminated with arsenic (As) is an important source of human As exposure through water-soil-rice transfer. While drinking water As has a permissible, or guideline value, quantification of guideline values for soil and irrigation water is limited. Using published data from 26 field studies (not pot-based experiments) from Asia, each of which reported irrigation water, soil and rice grain As concentrations from the same site, this meta-analysis quantitatively evaluated the relationship between soil and irrigation water As concentrations and the As concentration in the rice grain. A generalized linear regression model revealed As in soil to be a stronger predictor of As in rice than As in irrigation water (beta of 16.72 and 0.6, respectively, p < 0.01). Based on the better performing decision tree model, using soil and irrigation water As as independent variables we determined that Asian paddy soil As concentrations greater than 14 mg kg−1 may result in rice grains exceeding the Codex recommended maximum allowable inorganic As (i-As) concentrations of 0.2 mg kg−1 for polished rice and 0.35 mg kg−1 for husked rice. Both logistic regression and decision tree models, identified soil As as the main determining factor and irrigation water to be a non-significant factor, preventing determination of any guideline value for irrigation water. The seemingly non-significant contribution of irrigation water in predicting grain i-As concentrations below or above the Codex recommendation may be due to the complexity in the relationship between irrigation water As and rice grains. Despite modeling limitations and heterogeneity in meta-data, our findings can inform the maximum permissible As concentrations in Asian paddy soil.